FUNCTIONAL OUTCOME OF EXTRA-ARTICULAR DISTAL HUMERUS FRACTURE FIXATION USING A LATERAL COLUMN LOCKING COMPRESSION PLATE - Ghega, Araib; Effan, Farzad; Ansari, Hizbullah Riaz; Abdullah, Mohammad Tallal; Javaid, Shahzad; Aziz, Amer (Journal of Ayub Medical College Abbottabad, 2022)
Background: A host of different methodologies have been implemented in the management of distal humerus fractures, including conservative measures and surgical fixation with a variety of plates. This study was conducted to evaluate the functional outcome of open reduction and internal fixation of extra articular distal humerus fractures with distal humerus locking compression plate. Methods: This is a retrospective cohort study of patients with close extra articular distal humerus fractures who underwent open reduction and internal fixation with a distal humerus locking compression plate at Ghurki Trust Teaching Hospital from July 2017 to December 2019. Various demographic indicators were used for data analysis and radiological union was assessed in serial follow-ups. Functional outcome was evaluated using the Mayo Performance Elbow Score at the final follow-up. Results: Thirty-one patients presented with extra-articular fracture of humerus (N=31) with average age 33.5±9.90 years. The average follow-up period was 13.8 months. Radiological union was achieved in 14.8 weeks (range 12-20 weeks). Out of 31 patients, 28 had excellent results with mean Mayo Elbow Performance Score of 94.8. Two patients (6.5%) had radial nerve palsy post-operatively. Conclusion: This study shows that open reduction and internal fixation of extra-articular distal humerus fractures with distal humerus locking compression plates allows for stable fixation, good functional outcome, and low complication rates.